2004
DOI: 10.1103/physrevb.70.024408
|View full text |Cite
|
Sign up to set email alerts
|

Structural origin of dipole x-ray resonant scattering in the low-temperature phase ofNd0.5Sr0.5MnO3

Abstract: We have investigated the low temperature phase of a Nd 0.5 Sr 0.5 MnO 3 single crystal by x-ray resonant scattering at the Mn K-edge of the (3 0 0

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 59 publications
9
94
3
Order By: Relevance
“…[13][14][15][16][17] A RXS study at the Mn K edge of Nd 0.5 Sr 0.5 MnO 3 has shown that the charge segregation is much less than 1 electron, Mn 3.4+ and Mn 3.6+ for odd and even Mn, respectively. 18 This result seems to be reproduced in other half-doped manganites. [19][20][21] Simultaneous to the appearance of superlattice reflections associated to a charge modulation between both kinds of Mn atoms, forbidden reflections have also been observed in RXS experiments at the Mn K edge [13][14][15][16][17][18]22 due to the anisotropy of the atomic scattering tensor ͑so-called anisotropic tensor susceptibility or ATS reflections͒ The structure factor of those ATS reflections is given by the difference between odd-Mn atoms with different orientation of their anisotropy axis in the ab plane ͑Fig.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…[13][14][15][16][17] A RXS study at the Mn K edge of Nd 0.5 Sr 0.5 MnO 3 has shown that the charge segregation is much less than 1 electron, Mn 3.4+ and Mn 3.6+ for odd and even Mn, respectively. 18 This result seems to be reproduced in other half-doped manganites. [19][20][21] Simultaneous to the appearance of superlattice reflections associated to a charge modulation between both kinds of Mn atoms, forbidden reflections have also been observed in RXS experiments at the Mn K edge [13][14][15][16][17][18]22 due to the anisotropy of the atomic scattering tensor ͑so-called anisotropic tensor susceptibility or ATS reflections͒ The structure factor of those ATS reflections is given by the difference between odd-Mn atoms with different orientation of their anisotropy axis in the ab plane ͑Fig.…”
Section: Introductionsupporting
confidence: 63%
“…18 No contribution is expected from the anisotropy of the odd-Mn sublattice, as deduced from Eq. ͑3͒.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations